An Explorative Analysis of the Labour Market structure in the Peri-Urban area of Hyderabad Metropolitan Region - Thomas, Judy; Swamikannu, Nedumaran; Vijayakumari, R.; Nandi, Ravi (International Journal of Bio-resource and Stress Management, 2023)
The study was undertaken during June–August, 2020 in the peri-urban areas of Hyderabad Metropolitan Region of Telangana under the department of Agricultural Economics, Professor Jayashanker Telangana State Agricultural University, Rajendranagar, Hyderabad, Telengana state, India. The objective was to explore the nature of gender gap in the labour market since peri-urban spaces capture changes better. Based on the Census survey data, descriptive analysis was employed in the study. The study revealed that urban sprawl did not guarantee working environment to men and women equally and women were either pushed out of workforce or rendered with marginal works. A gendered society in developing world was clearly pictured and occupational segregation was also observed in the study locations. The results also revealed the existence of distress employment with a rise in the female marginal workers compared to their male counterparts. Women workers were more into agricultural labour than male workers in the peri-urban study locations confirming feminisation of agriculture whereas other worker category which needs specialized skills were dominated by male workers. A decline in female work participation rate was indeed observed but a detailed look identified it as a rural phenomenon. In a nut shell, the results reflected that the rapid developments in the peri-urban region did not provide a similar working environment to both genders and further, the benefits of urbanization is yet to reach the rural continuum.